2022
DOI: 10.1519/jsc.0000000000004189
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Global Myoelectric Spatial Activations to Delineate Normal Hamstring Function at Progressive Running Speeds: A Technical Report

Abstract: Schlink, BR, Nordin, AD, Diekfuss, JA, and Myer, GD. Quantification of global myoelectric spatial activations to delineate normal hamstring function at progressive running speeds: A technical report. J Strength Cond Res 36(3): 867–870, 2022—Hamstring function is critical to maintain sport performance, and strain injuries to the biceps femoris muscle commonly force an athlete to withdraw from their sport while the muscle heals. Current mechanistic understanding of underlying injury and return-to-play (RTP) guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Hamstring muscle activity during high‐speed running was previously assessed with multichannel EMG for the biceps femoris long head and semitendinosus 23,25 . These two studies investigated primarily the effect of running speed on the amplitude of normalized muscle activity within each muscle 23,25 . One of these studies reported within hamstring muscle activity distribution as a sub‐analysis 25 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hamstring muscle activity during high‐speed running was previously assessed with multichannel EMG for the biceps femoris long head and semitendinosus 23,25 . These two studies investigated primarily the effect of running speed on the amplitude of normalized muscle activity within each muscle 23,25 . One of these studies reported within hamstring muscle activity distribution as a sub‐analysis 25 .…”
Section: Discussionmentioning
confidence: 99%
“…23,25 These two studies investigated primarily the effect of running speed on the amplitude of normalized muscle activity within each muscle. 23,25 One of these studies reported within hamstring muscle activity distribution as a subanalysis. 25 In contrast to our findings, no differences were found among three regions within the biceps femoris long head and semitendinosus, when comparing muscle activity over a stride cycle during high-speed running.…”
Section: Comparison With Literaturementioning
confidence: 99%
See 3 more Smart Citations